Living in a dangerous climate : climate change and human evolution - Hetherington, Renée (Cambridge University Press, 2012)
"Living in a Dangerous Climate provides a journey through human and Earth history, showing how a changing climate has affected human evolution and society. Is it possible for humanity to evolve quickly, or is slow, gradual, genetic evolution the only way we change? Why did all other Homo species go extinct while Homo sapiens became dominant? How did agriculture, domestication, and the use of fossil fuels affect humanity's growing dominance? Do today's dominant societies - devoted as they are to Darwinism and "survival of the fittest"--Contribute to our current failure to meet the hazards of a dangerous climate? Unique and thought provoking, the book links scientific knowledge and perspectives of evolution, climate change, and economics in a way that is accessible and exciting for the general reader. The book is also valuable for courses on climate change, human evolution, and environmental science"--